Odpowiedzi

2010-03-23T20:06:49+01:00
A)2x-1+4x=2+8x-5
-2x=2/(-2)
x=-1
b)7-3x+4=x+1-2x-4
-3x-x+2x=7+1
-4x+2x=8
-2x=8/(-2)
x=-4
c) 4-10+2x=x-4x+4
2x+4x-x=-10
5x=-10/5
x=-2

d)x+3-4+x=3x-2x+3
2x+2x-3x=3-3+4
-x=4/-1
x=-4
Najlepsza Odpowiedź!
2010-03-23T20:06:52+01:00
A) 2x - (1-4x)=2+(8x-5)
2x-1+4x=2+8x-5
2x+4x-8x=2-5+1
-2x=-2|:-2
x=1

b) 7-(3x-4)=(x+1)-2x+4)
7-3x+4=x+1-2x-4
-3x-x+2x=1-4-7-4
-2x=14|-2
x=7

c) 4-2(5-x)=x-4(x-1)
4-10-2x=x-4x-4
-2x-x+4x=-4-4+10
x=2

d) x+3-(4-x)=3x-(2x-3)
x+3-4+x=3x-2x+3
x+x-3x+2x=3-3+4
x=4